INTERACTIVE METHODS IN TEACHING ENGLISH - Rashidova Aziza Musulmon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The teaching of English as a foreign language has evolved significantly over the years. Traditional methods have given way to more interactive and student-centered approaches. This paper explores the various interactive methods employed in English language teaching, highlighting their benefits, challenges, and practical applications. It examines techniques such as group work, role-playing, games, and technology-enhanced activities. The aim is to provide educators with insights into how to create engaging and effective learning environments that foster language acquisition and communication skills.